The incentive effects of missions—Evidence from experiments with NGO employees and students - Gerhards, Leonie (European economic review, 2015)
This paper studies the incentive effects of an organization׳s ‘mission’ on the effort provision of agents. Across treatments, I exogenously vary how much the agents׳ and their projects׳ missions match. In the first study, NGO employees are assigned the role of agents in an online, one-shot, principal-agent experiment. In the second study, I replicate the experimental design with a student subject pool. In both experiments the agents׳ effort choices are, for any given piece rate, increasing in their mission match. In a third study, a laboratory experiment with a finitely repeated principal-agent game with random matching, I do not find a motivational effect of missions, unlike in my first two studies.